Patient Characteristics, Financing Type, Accreditation Status, and Quality of Health Services at Community Health Center, Surakarta - Yeni Tri Utami; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2017)
Background: An indicator of quality health service is the extent of patient expectation fulfilment. Perceived quality of health services may be influenced by various factors such as patient socio-demographic factors, financing type, and accreditation status. As statistics have shown, the number of patient visits at Surakarta Community Health Center has been decresing for the last few years. This study aimed to determine the associations between patient characteristics, financing type, accreditation status, and the quality of  health services at community health center.Subjects and Method: This was a quantitative study with cross-sectional design. It was conducted at Community Health Center, Surakarta, Central Java, from May to July 2017. A sample of 120 patients were selected for this study from 2 Community Health Centers selected at random from all 17 Community Health Centers existing in Surakarta. The independent variables were patient characteristics, financing type, and accreditation status of the Community Health Centers selected. The dependent variable was quality of health service. The data were collected using a set of questionnaire and  analyzed using multiple logistic regression.Results: Quality of service was negatively associated with patient education (OR = 0.27 ; 95% CI = 0.08 to 0.90; p = 0.033), being employed (OR = 0.15 ; 95% CI= 0.04 to 0.48; p = 0.002), higher patient income (OR = 0.28 ; 95% CI= 0.08 to 0.94; p = 0.039), being insured (OR = 3.06 ; 95% CI= 0.81 to 11.52; p = 0.099), and higher accreditation status of Community Health Care (OR = 2.96 ; 95% CI= 1.03-8.50; p = 0.044).Conclusion: Quality of service at Community Health Care is negatively associated with patient education, being employed, higher patient income, being insured, and higher accreditation status.Keywords: patient characteristic, financing type, accreditation status, quality of servicesCorrespondence: Yeni Tri Utami. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: yenie_03@yahoo.co.id. Mobile: +6285642339053.Journal of Health Policy and Management (2017), 2(1): 79-90https://doi.org/10.26911/thejhpm.2017.02.01.07